2013
DOI: 10.1007/s00381-013-2093-9
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary spinal cord abscess as complication of lumbar puncture: a case-based update

Abstract: The index of suspicion for a pyogenic infection of the intramedullary space should be higher if progressive flaccid paralysis develops within a few days after a lumbar procedure. Nevertheless, the diagnosis may be challenging due to the rarity of this condition. Any misdiagnosis or delay of adequate treatment may lead to unfavorable outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…In those cases, the mechanism of infection is direct inoculation of germs into the spinal cord. 10,11 In children, intramedullary abscess formation is often a complication of congenital neuroectodermal infection, generally located in the lumbar segment. 12,13 S. aureus is the most frequent pathogen to cause bacterial ISCA, 6 the causative micro-organism in our case.…”
Section: Discussionmentioning
confidence: 99%
“…In those cases, the mechanism of infection is direct inoculation of germs into the spinal cord. 10,11 In children, intramedullary abscess formation is often a complication of congenital neuroectodermal infection, generally located in the lumbar segment. 12,13 S. aureus is the most frequent pathogen to cause bacterial ISCA, 6 the causative micro-organism in our case.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of the first description of intramedullary abscess formation reported that it occurred after spinal anesthesia following a penetrating trauma to the spinal cord [ 32 ]. Other authors have reported cases of penetrating injuries that were coincidental with intramedullary abscess formation after a stab wound [ 33 ], spinal puncture [ 34 , 35 ], and transpharyngeal stab injury [ 36 ], with the most likely mechanism of infection of direct introduction microorganisms into the spine.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 122 papers potentially pertaining to the topic of the study were enrolled in the full-text assessment for eligibility. In these 122 papers, we identified 58 papers regarding pediatric ISCA with the description on 64 cases [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ].…”
Section: Literature Searchmentioning
confidence: 99%
“…The course of ISCA can be divided into acute (<1 week), subacute (1–6 weeks), and chronic (>6 weeks) [ 44 ]. The most frequently observed manifestation was acute: 25 (39.06%) followed by 21 (32.81%) subacute cases.…”
Section: What Is Currently Known About Intramedullary Spinal Cord Abs...mentioning
confidence: 99%